2022
DOI: 10.1590/acb371203
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 peptide Ac2-26 mitigates ventilator-induced lung injury in acute respiratory distress syndrome rats and partly depended on the endothelial nitric oxide synthase pathway

Abstract: Purpose: Although mechanical ventilation is an essential support for acute respiratory distress syndrome (ARDS), ventilation also leads to ventilator-induced lung injury (VILI). This study aimed to estimate the effect and mechanism of Annexin A1 peptide (Ac2-26) on VILI in ARDS rats. Methods: Thirty-two rats were randomized into the sham (S), mechanical ventilation (V), mechanical ventilation/ Ac2-26 (VA), and mechanical ventilation/Ac2-26/L-NIO (VAL) groups. The S group only received anesthesia, and the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…As an important anti-inflammatory factor, IL-10 can inhibit the synthesis of proinflammatory cytokines, including TNF-α, IL-1β, and IL-6 [27]. As an endogenous glucocorticoid-regulated anti-inflammatory [28], Ac2-26 has been indicated to prompt the expression of IL-10 to regulate inflammation [29,30]. These results suggested that Ac2-26 ameliorated liver injury and protected liver function may be associated with anti-inflammation.…”
Section: Discussionmentioning
confidence: 94%
“…As an important anti-inflammatory factor, IL-10 can inhibit the synthesis of proinflammatory cytokines, including TNF-α, IL-1β, and IL-6 [27]. As an endogenous glucocorticoid-regulated anti-inflammatory [28], Ac2-26 has been indicated to prompt the expression of IL-10 to regulate inflammation [29,30]. These results suggested that Ac2-26 ameliorated liver injury and protected liver function may be associated with anti-inflammation.…”
Section: Discussionmentioning
confidence: 94%
“…Cunha, 56 et al demonstrated that acute lung injury (ALI), caused by the administration of endotoxin LPS in mice resulted in leukocyte infiltration, exacerbated production of inflammatory mediators and tissue damage. Treatment with Ac2-26 was able to decrease leukocyte migration, especially in the pulmonary connective tissue and alveoli, contributing to the regulation of inflammation.…”
Section: Gutmentioning
confidence: 99%
“…In this context, it has been shown that ANXA1 effectively interrupts the activation of the NF-κB signalling pathway, which is an important transcription factor responsible for the activation of cytokines and chemokines, with a protective effect on the progression of ALI. 56 It is known that one of the pathological mechanisms of posttransplant I/R is the excessive production of ROS. It has been shown that ANXA1, by regulating iNOS (inducible nitric oxide synthase) and eNOS (endothelial nitric oxide synthase) levels, is able to inhibit oxygen stress, TNF-α expression, inflammation and apoptosis and, consequently, improve alveolar-capillary permeability.…”
Section: Gutmentioning
confidence: 99%
“…Knockdown of AnxA1 enhanced the oxidative stress and in ammation in cigarette smoke extract (CSE)-induced bronchial epithelial cells, a chronic obstructive pulmonary disease in vitro model (Yu and Zhang, 2022). In addition, AnxA1 peptide Ac2-26 signi cantly suppressed the activity of NADPH oxidase and malondialdehyde to decrease oxidative stress, lung injury and epithelium apoptosis in acute respiratory distress syndrome rats (Ju et al, 2023). Besides, in the kidney following ischemic injury, AnxA1 limited ROS production and increased antioxidant enzymes to abrogate oxidative stress and attenuate tubular cell death, which nally preserves the kidney against the ischemia (Suliman et al, 2021).…”
Section: Introductionmentioning
confidence: 98%